Hydrothermal synthesis of nitrogen-doped carbon dots with real-time live-cell imaging and blood–brain barrier penetration capabilities - Lu SS (Dove Medical Press, 2016)
Shousi Lu,1,2 Shanshan Guo,1 Pingxiang Xu,1 Xiaorong Li,1 Yuming Zhao,1 Wei Gu,3 Ming Xue1 1Department of Pharmacology, Beijing Laboratory for Biomedical Detection Technology and Instrument, School of Basic Medical Sciences, Capital Medical University, 2China Rehabilitation Research Center, 3Department of Chemistry and Biology, School of Chemical Biology and Pharmaceutical Sciences, Capital Medical University, Beijing, China Abstract: Nitrogen-doped carbon dots (N-CDs) were synthesized using a one-pot hydrothermal treatment with citric acid in the presence of polyethylenimine. Transmission electron microscopy analysis revealed that the N-CDs were monodispersed and quasi-spherical with an average size of ~2.6 nm. Under ultraviolet irradiation the N-CDs emitted a strong blue luminescence with a quantum yield as high as 51%. Moreover, the N-CDs exhibited a negligible cytotoxicity and could be applied as efficient nanoprobes for real-time imaging of live cells. In addition, the ability of the N-CDs to cross the blood–brain barrier (BBB) in a concentration-dependent manner was demonstrated using an in vitro BBB model. Therefore, these PEI-passivated N-CDs with real-time live-cell imaging and BBB-penetration capabilities hold promise for traceable drug delivery to the brain. Keywords: hydrothermal synthesis, nitrogen-doped carbon dots, bioimaging